3(m-6)=6(m-1)

Simple and best practice solution for 3(m-6)=6(m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(m-6)=6(m-1) equation:


Simplifying
3(m + -6) = 6(m + -1)

Reorder the terms:
3(-6 + m) = 6(m + -1)
(-6 * 3 + m * 3) = 6(m + -1)
(-18 + 3m) = 6(m + -1)

Reorder the terms:
-18 + 3m = 6(-1 + m)
-18 + 3m = (-1 * 6 + m * 6)
-18 + 3m = (-6 + 6m)

Solving
-18 + 3m = -6 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
-18 + 3m + -6m = -6 + 6m + -6m

Combine like terms: 3m + -6m = -3m
-18 + -3m = -6 + 6m + -6m

Combine like terms: 6m + -6m = 0
-18 + -3m = -6 + 0
-18 + -3m = -6

Add '18' to each side of the equation.
-18 + 18 + -3m = -6 + 18

Combine like terms: -18 + 18 = 0
0 + -3m = -6 + 18
-3m = -6 + 18

Combine like terms: -6 + 18 = 12
-3m = 12

Divide each side by '-3'.
m = -4

Simplifying
m = -4

See similar equations:

| (3+5i)(2+3i)(7+4i)=0 | | -2(X-4)+5x=2(X+3)+X+3 | | 5x^2-9x-2=o | | 2x+4-5=3x+1 | | 5[8+(81)]= | | f+12=4 | | f+12=-4 | | 6x-3(7-2x)=14 | | 5-7.12-15= | | (9(m+5)-15)+(2(m-3)+4)= | | 6(7au)+u=36+u | | 3x-3(5-2x)=3 | | 8a^3+27b^3+64c^3=72abc | | 9(2X-1)=3(3x+3) | | 1p+2=-1 | | 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 |

Equations solver categories